Evaluation of different remineralization agents in the treatment of natural caries-affected dentin in permanent teeth - KARGÜL, BETÜL (My University, 2023)
BACKGROUND: In the preventive treatment protocol, providing remineralization of the tissue in demineralized dentin caries is an important step. OBJECTIVE: In this in vitro study, the effectiveness of remineralization agents in natural caries-affected dentin (NCAD) were investigated. METHODS: Forty caries slices were prepared from permanent molar dentin with International Caries Detection and Assessment System (ICDAS 2) (Code 3). The interventions with 8 days pH cycling were as follows: Deionized water (DW); 5% Sodium Fluoride (5% NaF) Varnish; Casein Phosphopeptide-Amorphous Calcium Fluoride Phosphate (CPP-ACFP); Calcium Glyserophosphate (CaGP) + Magnesium (Mg) + Xylitol. DIAGNOdent (Laser Fluorescence, LF), Surface Microhardness (SMH), and X-ray Fluorescence (XRF) Spectroscopy measurements were calculated before and after pH cycling. RESULTS: LF values decreased between 5% NaF, CCP-ACFP and CaGP. NCAD treated with 5% NaF, CaGP and CCP-ACFP exhibited statistically higher hardness compared to the control group. After 5% NaF application, SMH values were significantly higher than the others. There was no statistically significant difference between baseline and after pH cycling hardness of the control group. After cycling, XRF showed that Ca and P concentrations were increased in all groups. CONCLUSION: The application of agents used in the study could be recommended and promoted as a treatment option of caries dentin for conventional management of caries.
Keywords: Biyomedikal Mühendisliği; Mühendislik ve Teknoloji; Biomedical Engineering; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; Malzeme Bilimi; MALZEME BİLİMİ, BİYOMATERYAL; MÜHENDİSLİK, BİYOMEDİKAL; Engineering, Computing & Technology (ENG); ENGINEERING; MATERIALS SCIENCE; MATERIALS SCIENCE, BIOMATERIALS; ENGINEERING, BIOMEDICAL; Biyomalzemeler; Fizik Bilimleri; Biyomedikal mühendisliği; Biomaterials; Physical Sciences; Calcium glycerophosphate; casein phosphopeptide-amorphous calcium phosphate; fluoride; natural caries-affected dentin (NCAD); pH cycling; surface microhardness